BuildingSync: A schema for commercial building energy audit data exchange. (July 2021) - Long, Nicholas; Fleming, Katherine; CaraDonna, Christopher; Mosiman, Cory
Abstract: Numerous data formats exist to exchange building related information throughout a building's lifecycle; many are all-encompassing formats while some newer formats are focused on specific software data exchange between actors such as system to system, system to user, or user to user. Despite this, data format challenges occur during each iteration of a commercial building energy audit. To overcome these challenges, BuildingSync has been designed to harmonize building data exchange during building energy audits. The schema was developed to be interoperable to support various use cases such as reporting audits in an electronic format, tracking proposed, implemented, and discarded energy conservation measures, and storing building characteristics (at multiple levels) for audits, benchmarking, and building energy analysis. This article will review the commercial building data exchange landscape, detail the development of BuildingSync, and provide examples of its use in the built environment. Highlights: New schema with a focus on data needed for commercial building energy audits. Data model for defining energy conservation measures in commercial buildings. Unique data structure for storing the life cycle of energy conservation measures. Case studies showing how the new schema is being used in projects. Building data interoperability with range of high level to detailed representations.